Audit Quality Reduction Behavior: Locus Of Control, Job Stress, Time Pressure - I Gusti Ayu Ratih Permata DEWI; Putu Yudha Asteria PUTRI (International Journal of Environmental, Sustainability, and Social Science, 2020)
This study aims to examine the effect of locus of control and job stress on audit time budget pressure and its implications on the behavior of KAP audit quality reduction in Bali. Data used by using a questionnaire. The sample in this study amounted to 35 respondent. The data analysis technique used is path analysis. The test results show that locus of control and job stress has a positive effect on audit time budget pressure. Audit time budget pressure has a positive effect on quality reduction behavior in an audit. Furthermore, audit time budget pressure mediates the effect of locus of control and job stress on audit quality reduction behavior. The coefficient of the indirect effect of job stress on the behavior of the reduction of the quality of the audit through the budget pressure audits provides a greater effect than a direct effect of path coefficient value of job stress on the behavior of the reduction of the quality of the audit.